MINIMUM SPANNING TREE PADA JARINGAN PENDISTRIBUSIAN ANEKA KRIPIK ABDI MULYA DI KABUPATEN GROBOGAN - Rahmawati, Anita; Mulyono, Mulyono (Unnes Journal of Mathematics, 2015)
Prim's algorithm is an algorithm that can be used to find the minimum spanning tree (minimal spanning tree) in a weighted graph. In this study, TORA software used in helping to resolve the minimum spanning tree problem. The purpose in writing this essay (1) determine the form of graphs in the design of the distribution network in a variety of chips Mulya Abdi Grobogan; (2) determine the completion of the minimum spanning tree using Prim's algorithm and software TORA on Distribution Network Mulya Abdi Assorted chips in Grobogan. Collecting data in this study is done by taking primary data obtained from the Home Industry Mulya Abdi. From the data obtained can be arranged network image. Furthermore, from a network image can be obtained using a minimum spanning tree with Prim's algorithm and software TORA so it will be easier than if done manually. Based on the results of research and discussion, it can be concluded that the minimum spanning tree obtained by calculation using Prim's algorithm and software turns TORA 9,365 m. Advice can be given of the results of the study are expected to contribute to the home industry and home industry Mulya Abdi other in determining the distribution of its products.